ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sesti Yurfita Sari; Kirmizi Ritonga; Rusli - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to examine the relation of managerial ownership, institutional ownership, firm size, leverage, profitability and sales growth to earnings management. Earnings management as the dependent variable is measured by discretionary accrual using the Modified Jones Model. Purposive sampling method used for sampling and where 31 companies in the manufacturing category with the period 2010-2013 where selected as sample. The method of analysis used in this study is multiple regression analysis. The results shows that the managerial ownership, institutional ownership, leverage, and sales growth has significant effect on earnings management. Meanwhile, firm size, and profitability have no significant effect on earnings management.Keywords: management, ownership, leverage, profitability, and sales growth.